CATEGORY OF BLOOD PRESSURE OF HYPERTENSIVE ELDERLY WHO CONSUMES AMBON BANANA AND WATERMELON - Rahman, Irpan Ali; Fauziah, Neng Fitri; Noviati, Elis; Kusumawaty, Jajuk; Apipudin, Aap (Dian Nuswantoro Semarang, 2023)
The World Health Organization states that the elderly are a group of people aged over 60 years. The Elderly is a period in their life span that is in a decline phase both physically and cognitively. The fundamental problem in the elderly is health problems. The older you get, the more you are at risk of increased blood pressure, especially systolic blood pressure, while diastolic blood pressure can only increase until the age of 55 years. Objective: Knowing the blood pressure of hypertensive elderly who consume Ambon bananas and watermelons in the Working Area of the Ciamis Health Center. Methods: The research used for this research is a quantitative descriptive study using a cross-sectional design. The population in this study amounted to 1,008 people. The sampling technique in this study used simple random sampling, namely as many as 90 respondents. Results: Research on the habit of consuming Ambon bananas by 57 respondents (63.3), and the habit of consuming watermelon by 33 respondents (36.7). Conclusion: This study stated that of the 90 elderly who consumed Ambon bananas and watermelon, the majority of their blood pressure was in stage 1 (mild) category.